Control of axon branch dynamics by correlated activity in vivo. - Ruthazer, E; Akerman, C; Cline, H (2003)
To determine how patterned visual activity regulates the development of axonal projections, we collected in vivo time-lapse images of retinal axons from albino Xenopus tadpoles in which binocular innervation of the optic tectum was induced. Axons added branch tips with nearly equal probability in all territories, but eliminated them preferentially from territory dominated by the opposite eye. This selective branch elimination was abolished by blockade of N-methyl-D-aspartate receptors. These results describe a correlation-based mechanism by which visual experience directly governs axon branch dynamics that contribute to the development of topographic maps.